Mortality and cancer incidence in persons with Down's syndrome, their parents and siblings. - Hermon, C; Alberman, E; Beral, V; Swerdlow, A (2001)
A cohort study of 1425 persons with Down's syndrome (DS), and of their parents (447 mothers, 435 fathers) and siblings (1176), was set up to investigate death rates from various causes and cancer incidence patterns. In individuals with DS the all-cause death rate was six times that of the national population (SMR = 622: 95% CI 559-693), the excess being attributable to many different causes. These included: leukaemia (SMR = 1304: 95% CI 651-2334); diabetes mellitus (SMR = 982: 95% CI 267-2515); Alzheimer's disease (SMR = 22028: 95% CI 7137-51326); epilepsy (SMR = 1727: 95% CI 744-3403); and congenital anomalies (SMR = 4987: 95% CI 4175-5955). The overall survival showed marked improvements for successive birth cohorts, particularly at young ages. For mothers and fathers of persons with DS, all-cause death rates were 20% lower than national rates and there were no significant excesses from any specific cause. For siblings, all-cause death rates were similar to national rates; the only condition with a significantly raised mortality ratio was colo-rectal cancer (SMR = 793: 95% CI 216-2031), but this may well be a chance finding.